Pemanfaatan Laman BIPA Daring dalam Konteks Multimodalitas bagi Pemelajar BIPA - Syukron Ramadloni (Balai Bahasa Provinsi Riau, 2022)
The learning process with web media is closely related to the use of multimodality in learning because students use various modes at the same time. BIPA Online as a reference for BIPA activities has never been studied in a scientific study. The purpose of this study is to describe how the use of multimodality on the BIPA Online is used in BIPA learning process. The technique of collecting data is through direct observation of the BIPA Online manager. In addition, semiotic analysis was used when watching and the technique used was the note-taking technique. The research method applied is qualitative with descriptive analysis. The research findings revealed that the BIPA Online is rich in material with multimodality in its presentation. The teaching materials discussed on this web cionsist of five types of semiotic systems. The study of multimodality texts is one of the studies in semiotics.